Differences in Glucose Readings Between Right Arm and Left Arm Using a Continuous Glucose Monitor. (September 2022) - Kawakatsu, Sonoko; Liu, Xiaohan; Tran, Brandon; Tran, Brittany P.; Manzanero, Lucy; Shih, Eric; Shek, Allen; Lim, Jeremy J.
Objective: Continuous glucose monitoring (CGM) devices are used for evaluating real-time glucose levels to optimize diabetes management. There is limited information, however, on whether readings differ when a device is placed on the right versus the left arm. This study evaluated the mean difference in glucose levels between the right and left arm and the effect of unilateral arm exercise on this difference. The effect of an intermittent fasting diet on body fat percentage was also evaluated. Research Design and Methods: In a prospective trial, 46 adult volunteers self-selected into the intermittent fasting (IF; N = 23) or free-living (FL; N = 23) diet group and were randomized into a unilateral arm exercise group. Volunteers had CGM sensors placed simultaneously on both arms for 12-14 days. Results: The mean glucose level in the right arm was significantly higher than the left arm by 3.7 mg/dL ( P < .001), and this result was unaffected by diet or arm exercise. Glucose levels were in euglycemic range for 75.2% of the time in the right arm and 67.5% in the left arm ( P < .001). The change from baseline in body fat percentage between the IF and FL diet groups was not significant. Conclusions: Measured glucose level and time in euglycemic range differ per placement of the CGM device, and the implications of this difference should be considered in clinical practice and research.